Price Differentiation and Discrimination in Transport Networks - Adriaan Hendrik van der Weijde (Tinbergen Institute, 2014)
This paper analyzes the effects of price differentiation and discrimination by a monopolistic transport operator, which sets fares in a congestible network. Using three models, with different spatial structures, we describe the operators optimal strategies in an unregulated market, a market where price differentiation is not allowed (i.e., ticket prices must be the same for all users), and a market where price discrimination is illegal (i.e., ticket prices must only differ with the marginal external costs of users), and analyze the welfare effects of uniform and non-discriminatory pricing policies. The three models allow us to consider three different forms of price differentiation and discrimination in networks: by user class, by origin-destination pair, and by route. We generalize the existing literature, in which groups usually only differ in their value of time, and hence, there is no distinction between differentiation and discrimination. In our models, users may also have different marginal external costs; we show how these two differences interact. We also show how non-differentiated and non-discriminatory policies may increase or decrease welfare, and that non-discrimination can be worse than non-differentiation. The network models show that results obtained for a single-link network can be generalized to a situation where operators price-discriminate or differentiate based on users origins and destinations, but not directly to a situation in which differentiation is based on route choices.
Keywords: L11; L51; L91; R43; 330; price differentiation; price discrimination; transport; networks; congestion